2019
DOI: 10.3847/1538-4357/aafb6c
|View full text |Cite
|
Sign up to set email alerts
|

JCMT POL-2 and ALMA Polarimetric Observations of 6000–100 au Scales in the Protostar B335: Linking Magnetic Field and Gas Kinematics in Observations and MHD Simulations

Abstract: We present our analysis of the magnetic field structures from 6000 au to 100 au scales in the Class 0 protostar B335 inferred from our JCMT POL-2 observations and the ALMA archival polarimetric data. To interpret the observational results, we perform a series of (non-)ideal MHD simulations of the collapse of a rotating nonturbulent dense core, whose initial conditions are adopted to be the same as observed in B335, and generate synthetic polarization maps. The comparison of our JCMT and simulation results sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This spatial scale is also comparable to those probed by interferometric polarimetric observations with CARMA and SMA (e.g., Hull et al 2013Hull et al , 2014Galametz et al 2018). As shown in previous studies that compare single-dish and interferometric results (e.g., Hull et al 2014;Yen et al 2019;Doi et al 2020), single-dish measurements at stellar positions can generally present the mean orientations of magnetic field on small scales observed by interferometers. In 17 of our sample sources, the mean magnetic field orientations on a 1000 au scale were also measured with the CARMA, SMA, and/or Atacama Large Millimeter/ submillimeter Array (ALMA) observations (Hull et al 2014;Galametz et al 2018;Sadavoy et al 2019).…”
Section: Dependence Of the Misalignments On T Bol And Spatial Scalementioning
confidence: 53%
See 2 more Smart Citations
“…This spatial scale is also comparable to those probed by interferometric polarimetric observations with CARMA and SMA (e.g., Hull et al 2013Hull et al , 2014Galametz et al 2018). As shown in previous studies that compare single-dish and interferometric results (e.g., Hull et al 2014;Yen et al 2019;Doi et al 2020), single-dish measurements at stellar positions can generally present the mean orientations of magnetic field on small scales observed by interferometers. In 17 of our sample sources, the mean magnetic field orientations on a 1000 au scale were also measured with the CARMA, SMA, and/or Atacama Large Millimeter/ submillimeter Array (ALMA) observations (Hull et al 2014;Galametz et al 2018;Sadavoy et al 2019).…”
Section: Dependence Of the Misalignments On T Bol And Spatial Scalementioning
confidence: 53%
“…On the other hand, as the infalling and rotational velocities increase with decreasing radii in the protostellar sources, the small-scale magnetic fields could be shaped by the gas motions, as suggested by the interferometric studies (Hull et al 2014;Galametz et al 2018). In addition, several interferometric observations at high angular resolutions, which well resolved the magnetic field structures in the protostellar envelopes on a scale of hundreds of astronomical units, revealed tangled, pinched, and/or wrapped magnetic fields (Girart et al 2006;Stephens et al 2013;Rao et al 2014;Hull et al 2017Hull et al , 2017Hull et al , 2020Cox et al 2018;Maury et al 2018;Sadavoy et al 2018Sadavoy et al , 2019Kwon et al 2019;Le Gouellec et al 2019;Lee et al 2019;Yen et al 2019Yen et al , 2020Ko et al 2020). Our JCMT POL-2 results also show that in 11 of our sample The gray area represents the 1σ uncertainty of the distribution, assuming that there is a 10°uncertainty in each measurement of the misalignment.…”
Section: Comparison With Interferometric Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The magnetic field in B335 has been studied in the nearinfrared (Kandori et al 2020), and with ALMA (Maury et al 2018), JCMT (Yen et al 2019), and SOFIA (Zielinski et al 2021) polarization observations. Yen et al (2019) found that the large-scale magnetic field is aligned with the rotation axis (E-W) to within about 10°on the plane of the sky, but that the polarization vectors rotate by about 90°on small scales, suggesting a magnetic pinch. The ALMA observations (Maury et al 2018) probe the polarization on scales of 50-500 au at 1.3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the relative lack of distortion in L1527 and IC348-SMM2 is due to the youth of these outflows, ∼ 10 3 yr, compared to ∼ 2 × 10 4 yr in B335. POL-2 and ALMA polarisation observations of B335 support the presence of a field aligned with the outflow direction (Yen et al 2019). The Davidson et al (2011) sources are lower in mass than is CB 54, which houses multiple protostars.…”
Section: Comparison With Other Regionsmentioning
confidence: 76%